Effects of Gymnema inodorum Leaf Extract on the Alteration of Blood Coagulation Parameters and Platelet Count in Plasmodium berghei-Infected Mice. (11th March 2022) - Boonyapranai, Kongsak; Sarakul, Orawan; Somsak, Voravuth; Sukati, Suriyan
Abstract : Malaria remains highly prevalent and one of the major causes of morbidity and mortality in tropical and subtropical regions. Alteration of blood coagulation and platelets has played an important role and attributed to increased morbidity in malaria. Hence, this study was performed to investigate the efficacy of Gymnema inodorum leaf extract on Plasmodium berghei -induced alteration of blood coagulation parameters and platelet numbers in mice. Groups of ICR mice were inoculated with 1 × 10 7 parasitized red blood cells of P. berghei ANKA (PbANKA) and given orally by gavage with 100, 250, and 500 mg/kg of G. inodorum leaf extract (GIE). Chloroquine (10 mg/kg) was used as a positive control. Platelet count and blood coagulation parameters were measured. The results showed that PbANKA induced thrombocytopenia in mice as indicated by markedly decreased platelet count. Decreased platelet count had a negative correlation with the degree of parasitemia with R 2 value of 0.6668. Moreover, significantly (p < 0.05 ) shortened activated partial thromboplastin time was found in PbANKA-infected group, while prothrombin time and thrombin time were still normal. GIE gave significantly (p < 0.05 ) good results with respect to platelet count, compared with the results obtained from positive and healthy controls. Additionally, GIE reversed the alteration of blood coagulation parameters when compared to untreated mice. The highest efficacy of GIE was observed at a dose of 500 mg/kg. It was concluded that GIE exerted a protective effect on thrombocytopenia and altered blood coagulation parameters induced by PbANKA infection in mice. This plant may be a future candidate for alternative antimalarial development.